Neuroprotective Effect of Fisetin Through Suppression of IL-1R/TLR Axis and Apoptosis in Pentylenetetrazole-Induced Kindling in Mice - Khatoon, Saima; Agarwal, Nidhi Bharal; Samim, Mohammed; Alam, Ozair (Frontiers in Neurology, 2021)
Epilepsy is a complex neurological disorder, characterized by frequent electrical activity in brain regions. Inflammation and apoptosis cascade activation are serious neurological sequelae during seizures. Fisetin (3, 3′,4′,7-tetrahydroxyflavone), a flavonoid molecule, is considered for its effective anti-inflammatory and anti-apoptotic properties. This study investigated the neuroprotective effect of fisetin on experimental epilepsy. For acute studies, increasing current electroshock (ICES) and pentylenetetrazole (PTZ)-induced seizure tests were performed to evaluate the antiseizure activity of fisetin. For the chronic study, the kindling model was established by the administration of PTZ in subconvulsive dose (25 mg/kg, i.p.). Mice were treated with fisetin (5, 10, and 20 mg/kg, p.o.) to study its probable antiseizure mechanism. The kindled mice were evaluated for seizure scores. Their hippocampus and cortex were assessed for neuronal damage, inflammation, and apoptosis. Histological alterations were observed in the hippocampus of the experimental mice. Levels of high mobility group box 1 (HMGB1), Toll-like receptor-4 (TLR-4), interleukin-1 receptor 1 (IL-1R1), interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) were assessed in the hippocampus and cortex by ELISA. The immunoreactivity and mRNA expressions of nuclear factor-κB (NF-κB), cyclooxygenase-2 (COX-2), cytochrome C, and caspase-3 were quantified by immunohistochemical analysis and real-time PCR. Phosphorylation ELISA was performed to evaluate AkT/mTOR (mammalian target of rapamycin) activation in the hippocampus and cortex of the kindled mice. The results showed that fisetin administration increased the seizure threshold current (STC) in the ICES test. In PTZ-induced seizures, fisetin administration increased the latency for myoclonic jerks (MJs) and generalized seizures (GSs). In the PTZ-induced kindling model, fisetin administration dose-dependently suppressed the development of kindling and the associated neuronal damage in the experimental mice. Further, fisetin administration ameliorated kindling-induced neuroinflammation as evident from decreased levels of HMGB1, TLR-4, IL-1R1, IL-1β, IL-6, and TNF-α in the hippocampus and cortex of the kindled mice. Also, the immunoreactivity and mRNA expressions of inflammatory molecules, NF-κB, and COX-2 were decreased with fisetin administration in the kindled animals. Decreased phosphorylation of the AkT/mTOR pathway was reported with fisetin administration in the hippocampus and cortex of the kindled mice. The immunoreactivity and mRNA expressions of apoptotic molecules, cytochrome C, and caspase-3 were attenuated upon fisetin administration. The findings suggest that fisetin shows a neuroprotective effect by suppressing the release of inflammatory and apoptosis molecules and attenuating histological alterations during experimental epilepsy.